Studies on the Effect of Cadmium Compound on the Biochemical Parameters of Fresh Water Fish in Cirrhinus mrigala - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIn the present investigation the effect of cadmium sulphate on the histology of gill, liver and kidney were investigated in the edible freshwater fish Cirrhinus mrigala. Further its effects on glycogen and protein contents in the gills, liver and kidney were analysed. A significant decrease of glycogen content was registered in liver, gills and kidney of metal treated fishes when compared to their controls. Similarly, the protein levels were decreased in gills, liver and kidney of cadmium sulphate treated fishes when compared to their controls. The significance of biomarkers was discussed in this present study.